Role of Probiotics in Optimizing the Causal Treatment for Acute Peritonsillitis - V.I. Popovych (Zaslavsky O.Yu., 2016)
The article deals with the management of patients with tonsillitis and its complications. When considering the aspects of the treatment, the attention was paid to the problem of antibiotic-associated diarrhea, and it was recommended to combine the use of antibiotics with probiotic preparations. There are presented the data of a study on the possibilities of using living microbial cells of Bacillus subtilis (drug Subalin) as an addition to antibiotic therapy of peritonsillitis, peritonsillar abscess to prevent antibiotic-associated diarrhea and to improve the efficiency of the treatment.